SCPEP1+ basal cells are associated with the remodeling of oxidative stress signaling networks in idiopathic pulmonary fibrosis - Zhou, Xiang; Lu, Tong; Xu, Ran; Wang, Chenghao; Chen, Simiao; Chen, Jing; Chang, Xiaoyan; Li, Meifeng; Shi, Jiaxin; Xu, Chengyu; Zhao, Yupeng; Peng, Bo; et al. (Frontiers in Immunology, 2025)
BackgroundIdiopathic pulmonary fibrosis (IPF) is a chronic and fatal interstitial lung disease marked by progressive extracellular matrix accumulation and irreversible lung architecture remodeling. Oxidative stress (OS) plays a crucial role in IPF pathogenesis, yet its role across distinct cellular compartments and tissue microenvironments remains incompletely characterized.MethodsWe integrated single-cell RNA sequencing (scRNA-seq), spatial transcriptomics (stRNA-seq), and bulk RNA-seq datasets to comprehensively characterize oxidative stress activity across cellular and tissue scales in IPF lungs. Oxidative stress scores were calculated using multiple enrichment algorithms, and machine learning models (LASSO, Random Forest, Boruta, Bayesian, LVQ, Treebag) were applied to identify robust OS-related diagnostic biomarkers. Expression patterns were validated in public datasets and a bleomycin-induced C57BL/6 mouse model. Cell-cell communication and gene regulatory pathways were further explored using CellChat and pseudotime trajectory analysis.ResultsOxidative stress activity was significantly elevated in IPF lung tissue and specifically enriched in basal cells. Among 71 candidate OS-related genes, SCPEP1 emerged as the most robust biomarker, consistently upregulated across multiple datasets and experimental validation, with an AUC of 0.857 in the training cohort. SCPEP1 expression was spatially confined to airway-adjacent regions and highly specific to basal cells. SCPEP1+ basal cells exhibited transcriptional reprogramming enriched in Wnt signaling and developmental pathways, dynamic expression during early pseudotime progression, and engaged in multifaceted interactions with immune and stromal cells through pro-fibrotic and inflammatory signaling axes such as MIF-CD74, MDK-NCL, and ICAM1-ITGAL. Translationally, these findings may help prioritize redox-sensitive pathways and ligand–receptor interactions for further investigation. While SCPEP1 appears to be a promising candidate, its potential for patient stratification or therapeutic intervention remains to be confirmed through functional studies.ConclusionOur multi-omics integration revealed SCPEP1+ basal cells as central oxidative stress responders and communication hubs in IPF. These findings provide insights into ROS-driven epithelial remodeling and highlight SCPEP1 as a potential contributor to disease-associated pathways that warrants further exploration for its diagnostic or therapeutic relevance.